EVALUASI PENDIDIKAN PERSPEKTIF ISLAM (ANALISIS TAFSIR Q.S QAFF AYAT 17-18) - DWITRI STEPANILI (STAI Ma'had Aly Al-Hikam Malang, 2019)
This journal describes the Evaluation of Islamic Perspective Education. Assessment is intended to determine educational decisions, which consist of planning, management, process and follow-up of education, both involving individuals, groups and institutions. In this context, the assessment in Islamic perspective education is aimed at making decisions related to education truly in accordance with Islamic values so that the educational goals proclaimed can be achieved to the fullest. This evaluation system isÂ based on the evaluation system outlined by Allah SWT, in the Koran and explained in the Sunna, which was carried out by the Prophet Muhammad in the process of fostering Islamic treatises. This research is a type of library research (library research), because the data source that will be explored is more focused on the study of literature: the written texts. Therefore this researcher will emphasize a qualitative approach.